(untitled) (Jurnal Bahasa, 2008)
Critical discourse analysis (CDA) is a textual analysis version in the analysis of language-based data in humanities and social research. This widely used version offers a repeatable method capable of tackling the data regardless of the positionality and verifiability In religious discourse analysis (RDA), in particular Islamic texts analysis, there are researchers in Malaysia who applied CDA in their studies with some modifications. This article discusses the scopes and the limitations proposed by CDA in RDA. The selected version of CDA is the 3D Fairclough’s dimension. The issues of relevance and irrelevance of his CDA will be highlighted in particular the contradictions that it poses from the Islamic point of views. Subsequently, modifications made will be discussed.